Understanding the performance and mechanism of Mg-containing oxides as support catalysts in the thermal dry reforming of methane - Khairudin, Nor Fazila; Sukri, Mohd Farid Fahmi; Khavarian, Mehrnoush; Mohamed, Abdul Rahman (Beilstein Journal of Nanotechnology, 2018)
Dry reforming of methane (DRM) is one of the more promising methods for syngas (synthetic gas) production and co-utilization of methane and carbon dioxide, which are the main greenhouse gases. Magnesium is commonly applied in a Ni-based catalyst in DRM to improve catalyst performance and inhibit carbon deposition. The aim of this review is to gain better insight into recent developments on the use of Mg as a support or promoter for DRM catalysts. Its high basicity and high thermal stability make Mg suitable for introduction into the highly endothermic reaction of DRM. The introduction of Mg as a support or promoter for Ni-based catalysts allows for good metal dispersion on the catalyst surface, which consequently facilitates high catalytic activity and low catalyst deactivation. The mechanism of DRM and carbon formation and reduction are reviewed. This work further explores how different constraints, such as the synthesis method, metal loading, pretreatment, and operating conditions, influence the dry reforming reactions and product yields. In this review, different strategies for enhancing catalytic activity and the effect of metal dispersion on Mg-containing oxide catalysts are highlighted.
Keywords: carbon formation; catalyst development; dry reforming of methane; magnesium catalyst; mechanism